Retrospective analysis of prenatal ultrasound of children with Pompe disease - Yan-Lin Li; Li Zhen; Min Pan; Dong-Zhi Li (Elsevier, 2022)
Objective: The aim of this retrospective study is to determine the prenatal ultrasound markers of patients diagnosed postnatally with infantile-onset Pompe disease (IOPD). Materials and methods: This is a retrospective study of cases with a postnatal diagnosis of IOPD during a 5-year period. The medical file of the patients with IOPD was reviewed, and data regarding especially pregnancy were collected. Results: Second trimester fetal sonographic anatomical scan was performed in all 13 cases during pregnancy. Two cases (15.4%) were found to have a persistently open mouth at 23 weeks and 24 weeks, respectively. Serials follow-up ultrasound examinations demonstrated the same findings in the two cases. Third trimester ultrasound was also performed in all cases. Large heart was found in five cases (38.5%), and fetal echocardiography confirmed hypertrophic cardiomyopathy. Conclusion: Our results indicate that a mid-trimester open mouth and third-trimester hypertrophic cardiomyopathy are the prenatal findings associated with the disorder of IOPD.